Sonographic and histopathological findings in ovarian dermoid cyst - Jaiswal, Pooja; Bhandary, Shital; Shrestha, Shreejana; Dwa, Yogita; Parmar, Binod; Karki, Dan B (Journal of Patan Academy of Health Sciences, 2017)
Introductions: Ovarian dermoid cyst occurs most commonly in reproductive age group. It consists all three layers of germ cells, in variable composition resulting in wide spectrum of USG findings. This study aimed to find the association between sonographic and histopathological findings of dermoid cyst. Methods: This was a retrospective study consisting of 55 cases of complex ovarian cysts with features of dermoid cyst, during two years 2013-2015. The diagnostic accuracies of trans-abdominal sonography findings were compared with post-operative histopathology reports. Results: Among 55 cases of complex ovarian cyst with sonographic features of dermoid, histopathology was benign in 52 (94.5%) and malignant in 3 (5.5%). In 52 benign cysts, 25 (48.0%) were teratoma and 27 (51.9%) were other benign masses. Conclusions: The accuracy of ultrasound was 95% in the diagnosis of ovarian cyst and is the modality of choice for initial workup of ovarian mass.